Breakup characteristics of high speed liquid jets from a single-hole injector. (1st April 2021) - Wu, Shengqi; Meinhart, Mark; Petersen, Benjamin; Yi, Jianwen; Wooldridge, Margaret
Highlights: Three empirical equations for predicting spray penetration were studied. Breakup characteristics of liquid jets at various pressures were investigated. Nozzle diameter affected the breakup time and length greatly. The initial spray penetration was proportional to injection time of GDI sprays. The initial jet velocity can be estimated based on the nozzle static flow rate. Abstract: In this study, spray characteristics from a single-hole gasoline direct injection injector with nozzle diameters of 0.14 mm and 0.2 mm were investigated. High-speed macroscopic and microscopic imaging techniques were applied to record the overall spray structure and the initial fuel spray behavior. The injection pressure ranged from 50 bar to 350 bar, and the ambient pressure was kept constant at 1 bar. Several semi-empirical models for predicting spray penetration at non-evaporating conditions were investigated, including models by Dent, Hiroyasu and Arai, and Naber and Siebers. Results showed that the Naber and Siebers equation demonstrated the best match with the experimental data. Both the initial and global spray penetration were well predicted. The spray penetration can be divided into two regions based on the relationship between spray penetration and injection time, namely the regions before and after breakup, and the transitional point was defined as the breakup point. Higher fuel pressures resulted in shorter breakup time and length for the injector with the smaller nozzle diameter, and the injector with larger nozzle diameter produced shorter breakup time and longer breakup length. A linear relationship was identified between the initial spray penetration and injection time at all fuel pressures, which indicates the initial spray tip velocity can be treated as constant at each fuel pressure. The ratio between the slope of experimental initial spray penetration and average flow velocity (based on static flow rate measurements) was around 0.9 at all fuel pressures for the injector with 0.14 mm nozzle diameter. Consequently, the average flow velocity obtained based on the static flow rate at each fuel pressure can be used to accurately predict the initial jet velocity.